2017
DOI: 10.18632/oncotarget.22608
|View full text |Cite
|
Sign up to set email alerts
|

Current research on head and neck cancer-associated long noncoding RNAs

Abstract: Head and neck cancers (HNC) are one of the ten leading cancers worldwide, including a range of malignant tumors arising from the upper neck. Due to the complex mechanisms of HNC and lack of effective biomarkers, the 5-year survival rate of HNC has been low and the mortality rate has been high in recent decades. Long noncoding RNAs (lncRNAs), noncoding RNAs longer than 200 bps, are a focus of current cancer research, closely related to tumor biology. LncRNAs have been revealed to be aberrantly expressed in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 173 publications
(315 reference statements)
0
13
0
Order By: Relevance
“…Among other things, functional non-coding RNAs are known to regulate the expression of protein-coding genes, and are involved in the maintenance of genome integrity [38,39]. Of relevance to this study, several long non-coding and small nucleolar RNAs have been found to be deregulated in head and neck squamous cell carcinoma [40,41], a cancer type strongly associated with tobacco smoking [42]. It has been suggested that these regulatory non-coding RNAs may drive malignant transformation by influencing cancer cell viability and motility [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Among other things, functional non-coding RNAs are known to regulate the expression of protein-coding genes, and are involved in the maintenance of genome integrity [38,39]. Of relevance to this study, several long non-coding and small nucleolar RNAs have been found to be deregulated in head and neck squamous cell carcinoma [40,41], a cancer type strongly associated with tobacco smoking [42]. It has been suggested that these regulatory non-coding RNAs may drive malignant transformation by influencing cancer cell viability and motility [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The use of new technologies to investigate tumor behavior and microenvironment is of great interest in this era of precision medicine. Several studies unraveled the role of molecular biomarkers for the diagnostic and therapeutic process in patients with OSCC [2426]. The application of “biologic endoscopy” to intraoperative surgical procedures represents another step forward towards the realization of the potentials of customized surgery [9, 10, 27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Next-generation sequencing has identified tens of thousands of lncRNAs from single-cell eukaryotes to humans [8]. LncRNAs are expressed in a tissue and cell-type specific manner, making them potential cancer biomarkers [4] and many SCCHN-related lncRNAs have been reported based on differential expression at a given significance level [9,10], even if the function of these disease-associated lncRNAs is largely unknown.…”
Section: Introductionmentioning
confidence: 99%